2019
DOI: 10.1016/j.amjmed.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Outcomes with Urate-Lowering Therapy: A Site-Randomized Trial

Abstract: Purpose: To test a pharmacist-led intervention to improve gout treatment adherence and outcomes. Methods: We conducted a site-randomized trial (n=1,463 patients) comparing a one-year, pharmacist-led intervention to usual care in gout patients initiating allopurinol. The intervention was delivered primarily through automated telephone technology. Co-primary outcomes were the proportion of patients adherent (proportion of days covered ≥0.8) and achieving a serum urate <6.0 mg/dl at one year. Outcomes were reasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 40 publications
0
38
0
1
Order By: Relevance
“…Similarly to our study, inthe RamP-UP study, patients were contacted directly by pharmacists (7). The SUA goal of ≤6 mg/dl was achieved in 30% of patients in the intervention group, in comparison to only 15% in the usual care group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly to our study, inthe RamP-UP study, patients were contacted directly by pharmacists (7). The SUA goal of ≤6 mg/dl was achieved in 30% of patients in the intervention group, in comparison to only 15% in the usual care group.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacist-and nurse-led telemedicine programs aimed at improving gout-related outcomes havebeen shown to not only improve medication compliance but have also demonstrated effectiveness in increasing the proportion of patients achieving goal SUA level of£6 mg/dl (7,8). However, to date, healthcare utilization and patient satisfaction with telemedicine programs havenot been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Doherty, et al 21 have shown outstanding effect on attainment and maintenance of target SU of close supervision of patients with gout receiving ULT by trained nurses, but resourcing this approach on a large scale is challenging. Pharmacists, who are often well-placed to monitor medication adherence, offer a potentially cost-effective approach to improving outcomes for patients 22,23 .…”
Section: Predictors Of Success In Gout Treatmentmentioning
confidence: 99%
“…Наш опыт обучающих мероприятий для пациентов позволяет согласиться, что подробная информация о подагре, в том числе о принципах ее лечения и самоконтроля, которую сообщает ревматолог, улучшает приверженность терапии и возможность достижения ее целей [39]. Аналогичные выводы были сделаны в ряде работ [40][41][42], в которых обучение пациентов проводилось медицинскими сестрами или фармакологами. Тем не менее метод получения пациентом информации имеет второстепенное значение [39], что подчеркивает условность рекомендации.…”
Section: «предоставление для оптимизации терапии средним медицинским unclassified